P609 Uncertain usefulness of infliximab trough levels for therapeutic decision-making in inflammatory bowel disease patients on infliximab maintenance therapy. (16th January 2018) - Cañete, F; Lobatón, T; Cabré, E; Mañosa, M; Teniente, A; Clos, A; Torres, P; Valldosera, G; Martínez-Cáceres, E; Domènech, E
Abstract: Background: It has been suggested that infliximab (IFX) trough levels (ITL) may be useful in different clinical settings in inflammatory bowel disease (IBD) such as secondary loss of response, prevention of primary non-response or even in clinically stable patients on maintenance therapy. However, to date, no controlled study has demonstrated its usefulness in clinical practice. Our aim was to assess the economic and clinical impact of the additional use of ITL in therapeutic decision-making in unselected IBD patients on IFX maintenance therapy. Methods: IBD patients on IFX maintenance therapy were consecutively included between June 2015 and June 2016. Blood samples for ITL (Sanquin Diagnostics) were collected at alternate infusions prior to IFX administration. According to clinical practice, patients were evaluated at that time based on the clinical symptoms and biomarkers of the same day (blood count, CRP) and recent imaging examinations, and a "basic therapeutic decision" (BTD) was taken by the physician in charge (no changes/dose escalation/spacing the dose/stopping due to sustained remission/switch or surgery). Once ITL were obtained, 3 expert physicians took a "hypothetical" therapeutic decision (blinded for BTD) according to the same clinical and biological data plus the results of ITL (TD-ITL). Only in those cases in which there was discrepancy between BTD and any of the 3 TD-ITL, the clinical outcomes occurred within 12 months following BTD were recorded and the impact of TD-ITL was classified as: unnecessary expense, cost saving, clinical benefit, or clinical harm. Those patients in whom treatment was stopped due to adverse events or those who were lost of follow-up were excluded. Results: We included 219 BTD from 72 patients (median duration of treatment 23 months [7–61], 18% of the BTD had clinical activity and 23% had CRP > 5 mg/dl). Among a total of 657 TD-ITL taken by the three experts, 280 (43%) were discordant with the BTD, but 28 were not evaluable. Within the following 12 months, 172 (68%) BTD were followed by no therapeutic changes and 80 (32%) underwent therapeutic changes. At the end of follow-up, TD-ITLs were qualified as: 162 (64%) unnecessary expense, 34 (13%) probable cost saving, 24 (10%) probable clinical benefit, 19 (7%) clinical benefit, 7 (3%) cost saving, 4 (2%) probable clinical damage, and 2 (1%) probable unnecessary expense. Conclusions: The use of ITL in therapeutic decision-making in unselected IBD patients on infliximab maintenance therapy significantly changes the therapeutic decisions, involving much more unnecessary expenses than clinical benefits. For this reason, its use in routine clinical practice should not be recommended.